Enhanced photocatalytic performance of a stable type-II PtSe2/GaSe van der Waals heterostructure - Parmar, P R; Khengar, S J; Sonvane, Yogesh; Thakor, P B (Physical chemistry chemical physics : PCCP, 2023)
In this investigation, the structural, electronic, and optical properties of two-dimensional van der Waals heterostructure (vdwHS) PtSe2/GaSe with three different configurations have been studied using density functional theory with the generalized gradient approximation. All three optimized vdwHSs PtSe2/GaSe have positive phonon frequencies and hexagonal unit cells. The hybrid exchange-correlation functional has been employed to study the electronic properties of vdwHSs PtSe2/GaSe. The vdwHSs PtSe2/GaSe shows semiconducting behavior with indirect Type-II bandgaps, which have been confirmed by the charge density difference, electrostatic potential, work function, and band edge calculations. Additionally, from the band edge positions, the vdwHSs PtSe2/GaSe are analyzed for photocatalytic activities. The optical properties such as extinction coefficient, refractive index, reflectivity, energy loss spectrum, and absorption coefficient have been studied using norm-conserving pseudo-potentials. The vdwHSs PtSe2/GaSe exhibit consistent absorption from the visible to the ultraviolet region of the electromagnetic spectrum. From the obtained results, we conclude that vdwHSs PtSe2/GaSe could be utilized for H2 production through photocatalytic activity as well as for optoelectronic devices and their application.In this investigation, the structural, electronic, and optical properties of two-dimensional van der Waals heterostructure (vdwHS) PtSe2/GaSe with three different configurations have been studied using density functional theory with the generalized gradient approximation. All three optimized vdwHSs PtSe2/GaSe have positive phonon frequencies and hexagonal unit cells. The hybrid exchange-correlation functional has been employed to study the electronic properties of vdwHSs PtSe2/GaSe. The vdwHSs PtSe2/GaSe shows semiconducting behavior with indirect Type-II bandgaps, which have been confirmed by the charge density difference, electrostatic potential, work function, and band edge calculations. Additionally, from the band edge positions, the vdwHSs PtSe2/GaSe are analyzed for photocatalytic activities. The optical properties such as extinction coefficient, refractive index, reflectivity, energy loss spectrum, and absorption coefficient have been studied using norm-conserving pseudo-potentials. The vdwHSs PtSe2/GaSe exhibit consistent absorption from the visible to the ultraviolet region of the electromagnetic spectrum. From the obtained results, we conclude that vdwHSs PtSe2/GaSe could be utilized for H2 production through photocatalytic activity as well as for optoelectronic devices and their application.